Population Pharmacokinetics of Adjunctive Lacosamide in Pediatric Patients With Epilepsy. (14th November 2018) - Winkler, Julia; Schoemaker, Rik; Stockis, Armel
Abstract: A pediatric population pharmacokinetic model including covariate effects was developed using data from 2 clinical trials in pediatric patients with epilepsy (SP0847 and SP1047). Lacosamide plasma concentration‐time data (n = 402) were available from 79 children with body weights ranging from 6 to 76 kg, and a balanced age distribution (6 months to <2 years: n = 14; 2 to <6 years: n = 22; 6 to <12 years: n = 25; 12 to <18 years: n = 18). A single‐compartment population pharmacokinetic model with first‐order absorption and elimination described the data adequately. Plasma clearance was modeled using allometric scaling on body weight with a freely estimated allometric exponent, while volume of distribution used a fixed theoretical allometric exponent. Covariate search identified a significant effect of enzyme‐inducing antiepileptic drugs resulting in a 35% decrease in lacosamide average plasma concentration. No additional effects on clearance could be attributed to race, sex, age, or renal function. Different dosing adaptation schemes by body weight bands were simulated to approximate, in pediatric patients aged 4 to 17 years, the same average plasma concentration as in adult patients receiving the maximum recommended lacosamide daily dose.